Counseling in Improving the Quality of Life of the Senior Population: Creating Action Opportunities - Cindy Vanessa Artavia-Aguilar; Manuel Arturo Fallas-Vargas (Revista Electrónica Educare)
In view of the constant demographic changes and the accelerated growth of the senior population in our country, it becomes necessary to create and enhance appropriate Counseling opportunities. It is necessary to pursue, at any time, the personal satisfaction, fulfillment and best quality of life for the elderly population through their active participation and self-awareness, and by developing social aspects that will contribute to their growth as a complete and socially active person. In order to face the cultural changes and the actual demands of our senior population, Counselors should be open to new intervention approaches that will help them to respond to social and personal emergent needs.